PENGARUH PENGATURAN POSISI TERHADAP LAMA PEMULIHAN KEADAAN PASIEN POST OPERASI DENGAN ANESTESI UMUM DI RECOVERY ROOM RSAM BUKITTINGGI - Mera Delima; Kalpana Kartika; Dewi Deswita (JURNAL KESEHATAN PERINTIS, 2019)
Background: Surgery is an option to address disease or health problems in modern medicine practice. After the surgery, the nurse checks the patient's condition and treats it in the recovery room. The phenomenon found in the field that there are some patients in recovery room with a recovery period of more than 1 day even reach 3-4 days. The purpose of this research is to know the effect of positioning on the recovery of patient condition in recovery room. Methods: Type of pre-experimental design study, with static group comparison design (Static Group Comparison). Population were all postoperative patients with general anesthesia treated in recovery room Methods of sampling using total sampling technique, amounted to 30 people. Processing and data analysis is done computerized. Result: The univariate analysis result showed that the average recovery time of the patient who performed positioning every 15 - 30 minutes was 1.67 days, and the non-positioning was 2.73 days. Bivariate results have effect of position setting on recovery of patient condition in recovery room (p = 0,011). Conclusion and Suggestion: It is concluded that there is an effect of positioning on the recovery of the patient's condition in recovery room. It is expected that officers should make position arrangements every 15 - 30 minutes to accelerate the recovery of postoperative patients under general anesthesia